Comparative Imaging Study in Ultrasound, MRI, CT and DSA using a Multi-Modality Renal Artery Phantom - FAGAN, ANDREW (My University, 2011)
Purpose: A range of anatomically-realistic multi-modality renal artery phantoms consisting of vessels with varying degrees of stenosis was developed and evaluated using four imaging techniques currently used to detect renal artery stenosis (RAS). The spatial resolution required to visualize vascular geometry and the velocity detection performance required to adequately characterize blood flow in patients suffering from RAS is currently ill-defined, with the result that no one imaging modality has emerged as a gold standard technique for screening for this disease. Methods: The phantoms, which contained a range of stenosis values (0, 30, 50, 70 and 85%), were designed for use with ultrasound, magnetic resonance imaging, X ray computed tomography and X-ray digital subtraction angiography. The construction materials used were optimized with respect to their ultrasonic speed of sound and attenuation coefficient, MR relaxometry (T1, T2) properties, and Hounsfield number / X-ray attenuation coefficient, with a design capable of tolerating high-pressure pulsatile flow. Fiducial targets, incorporated into the phantoms to allow for registration of images among modalities, were chosen to minimize geometric distortions. Results: High quality distortion-free images of the phantoms with good contrast between vessel lumen, fiducial markers and background tissue to visualize all stenoses were obtained with each modality. Quantitative assessments of the grade of stenosis revealed significant discrepancies between modalities, with each underestimating the stenosis severity for the higher-stenosed phantoms (70% and 85%) by up to 14%, with the greatest discrepancy attributable to DSA. Conclusions: The design and construction of a range of anatomically-realistic renal artery phantoms containing varying degrees of stenosis is described. Images obtained using the main four diagnostic techniques used to detect RAS were free from artifacts and exhibited adequate contrast to allow for quantitative measurements of the degree of stenosis in each phantom. Such multi-modality phantoms may prove useful in evaluating current and emerging US, MRI, CT and DSA technology.
PUBLISHED
Keywords: multi-modality; ultrasound; phantom; in vitro experimentation; Next Generation Medical Devices